Assessment of Urinary Dysfunction After Midurethral Sling Placement: A Comparison of Two Voiding Trial Methods - Leffelman, Angela; Chill, Henry H; Kar, Ayesha; Gilani, Sonia; Chang, Cecilia; Goldberg, Roger P; Rostaminia, Ghazaleh (Journal of minimally invasive gynecology, 2024)
Temporary urinary retention after midurethral sling (MUS) surgery requiring indwelling catheter or self-catheterization usage is common. Different methods for assessment of immediate postoperative urinary retention have been described. This study aimed to compare postoperative voiding trial (VT) success after active vs passive VT in women undergoing MUS surgery. Comparative retrospective cohort study. Female pelvic medicine and reconstructive surgery practice at a university-affiliated tertiary medical center. Patients with stress urinary incontinence who underwent surgical treatment during the study period were eligible for inclusion. Excluded were patients younger than the age of 18 years, combined cases with other surgical services, planned laparotomy, and a history of urinary retention and patients for whom their VT was performed on postoperative day 1. The cohort was divided into 2 groups: (1) patients who underwent an active retrofill of their bladder using a Foley catheter and (2) patients who were allowed to have a spontaneous void. None. A total of 285 patients met the inclusion criteria for the study. Of these subjects, 94 underwent an active VT and 191 underwent a passive VT. There were no statistically significant differences in immediate postoperative urinary retention (30.8% vs 29.3%; p = .79) or time from surgery end to VT (233.0 ± 167.6 minutes vs 203.1 ± 147.8 minutes; p = .13) between groups. Urinary retention, as defined by a failed VT, increased from 10% to 29.3% when MUS placement was accompanied by concomitant prolapse repair procedure. Multivariate logistic regression analysis revealed that undergoing a combined anterior and posterior colporrhaphy (odds ratio [OR], 5.13; p <.001) and undergoing an apical prolapse procedure (OR, 2.75; p = .004) were independently associated with immediate postoperative urinary retention whereas increased body mass index (OR, 0.89; p <.001) lowered likelihood of retention. The method used to assess immediate postoperative urinary retention did not affect VT success. Concomitant combined anterior and posterior colporrhaphy and apical suspension were correlated with greater likelihood of VT failure whereas increased body mass index decreased odds of retention.